“The Spectacle of a Young Man”: Glenn Gould, Graham Steed, and an Unpublished Concert Review for the Windsor Star - Reul, Barbara (Intersections)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 2013)
This article focuses on the content, intent, and historical context of an unpublished review of a concert performed by Glenn Gould and the Detroit Symphony Orchestra in Detroit, Michigan, on 13 October 1960. The review is preserved at the Library and Archives Canada and was written by Graham Steed (1913–1999). This respected British-Canadian organist and scholar served as the Windsor Star’s music critic from 1959 to 1965. Interestingly, Steed’s American colleagues reviewed Gould’s performance favourably. In contrast, Steed’s own highly controversial critique was deemed unfit for public consumption by the editor of the Windsor Star.